O-17 Legal needs towards end of life: definition, experience and implications for policy and practice. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Hawkins, Colette; Close, Helen; Kirby, Margaret; Hesselgreaves, Hannah; Rothwell, Charlotte; Beardon, Sarah; Genn, Hazel
Abstract : Background: Life-limiting illness generates an array of challenges for patients and carers but little is known about legal issues. There is no definition of legal issues in this context and limited integration of care across health, social, advice, legal and charitable sectors although all contribute to holistic care. Aims: The Legal Needs of Adults towards End of Life (LeNA) project investigated the scope and scale of legal needs from a range of perspectives, the support structures available and professional education needs with a view to shaping national policy. Methods: Sept 2017 – June 2018: systematic literature review and national stakeholder engagement exercise across health, social, charitable, advice and legal services: definition of legal needs, available support and gaps. May 2018 – March 2019: semi-structured interviews (24 patient/carer) and questionnaires (124 patient/carer/staff) to evaluate experience of legal needs. Sept 2018 – Jan 2019: four inter-professional workshops to consider educational needs through a taster session and focus groups (6). Results: Legal needs are very broad and practice highly variable. The project has developed a classification relating to patient/carer rights and professional responsibilities. This could direct future policy. Patients and carers struggle with unmet needs, uncertain of how to access help and unwilling to plan for the future in the context of active concerns. Some support structures already exist but the project identified a number of barriers and consideration needs to be given to accessibility and suitability of these. There is significant enthusiasm for widely inter-professional education in this area, using an interactive group structure. Conclusions: Legal needs are poorly defined in palliative care, resulting in variability in practice and unmet need. This is an area for improvement and follow-on research is planned at national policy level. Together with novel education, this will support better assessment and integrated care around legal needs towards end of life.